Cultural heritage and energy transition – A lesson from the past - Xavier Casanovas; José A. Alonso Campanero; Tiziana Campisi (Agathón)
In the complex landscape of energy transition, Cultural Heritage emerges as a fundamental pillar of ‘innovability’, suggesting a lesson from the past. Historically, technical culture has been able to adapt building wisdom to available energy resources, demonstrating surprising resilience and an innate propensity for innovation. The energy adaptation associated with conserving this heritage must preserve the Mediterranean identity this essay aims to address; traditional technologies are still relevant today, while modern energy technologies require harmonious integration. This symbiosis between past and present is of crucial practical and symbolic importance: reconnecting with our cultural roots in moving towards a more sustainable future ensures a painless path to energy efficiency.